Synthesis, Spectroscopic and Dyeing Performance Studies of Some New Heterocyclic Azo Dyes and Their Complexes with Selected Metal Ions - Al-Hasani, T. J.; Jarad, A. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Coupling reaction of m-and p- amino acetophenone and p-amino benzoic acid with (L- Histidine) gave the new bidentate azo ligands (L1, L2 and L3). The prepared ligands were identified by FT-IR, UV-Vis, 1HNMR and GC- mass spectroscopic technique. Treatment of the prepared ligands with the following metal ions (CoII, NiII, CuII, ZnII, CdII and HgII) in aqueous ethanol with a 1:2 M:L ratio and at optimum pH, yielded a series of neutral complexes of the general formula [M(L)2 Cl2]. The prepared complexes were characterized by using flame atomic absorption, FT-IR, UV-Vis and 1HNMR spectroscopic methods as well as magnetic susceptibility and conductivity measurements. Chloride ion content was also evaluated by (Mohr method). The nature of the complexes formed was studied following the mole ratio and continuous variation methods, Beer's law obeyed over a concentration range (1Ã— 10-4- 3 Ã— 10-4M). High molar absorbtivity of the complex solutions was observed. The stability constant of the complexes have also been studied.  In addition the dyeing performance of the prepared ligands and some of their complexes was applied on cotton fabric. The dyes were tested for light and detergent fastness. Biological activity of the ligands and complexes against three selected types of bacteria was also examined. Some of the complexes exhibit good bacterial activities.